2024
DOI: 10.1124/jpet.123.001742
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Arsenical Exposure Induces Distinct Metabolic Transcriptional Alterations of Kidney Cells

Kyle H. Moore,
Laurence M. Boitet,
Darshan S. Chandrashekar
et al.

Abstract: Arsenicals are deadly chemical warfare agents which primarily cause death through systemic capillary fluid leakage and hypovolemic shock. Arsenical exposure is also known to cause acute kidney injury, a condition that contributes to arsenical-associated death due to the necessity of the kidney in maintaining whole-body fluid homeostasis. Because of the global health risk that arsenicals pose, a nuanced understanding of how arsenical exposure can lead to kidney injury is needed. We utilized a non-targeted trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While antidotes like British anti-Lewisite exist, their limited application and potential toxic side effects underscore the urgent need for more effective treatments against arsenical exposure. George and colleagues explored the transcriptomic effects of cutaneous exposure to PAO, a common arsenical, on the kidneys of mice ( Moore et al, 2024 ). They found that PAO exposure upregulates metabolic pathways, such as fatty acid oxidation and PPAR-α signaling, and genes in proximal tubule epithelial cells and endothelial cells.…”
Section: Metabolic and Cellular Agentsmentioning
confidence: 99%
“…While antidotes like British anti-Lewisite exist, their limited application and potential toxic side effects underscore the urgent need for more effective treatments against arsenical exposure. George and colleagues explored the transcriptomic effects of cutaneous exposure to PAO, a common arsenical, on the kidneys of mice ( Moore et al, 2024 ). They found that PAO exposure upregulates metabolic pathways, such as fatty acid oxidation and PPAR-α signaling, and genes in proximal tubule epithelial cells and endothelial cells.…”
Section: Metabolic and Cellular Agentsmentioning
confidence: 99%
“…CoN4[14] is presented as a promising antidote for cyanide and azide poisoning (Pearce et al, 2024a). Studying metabolic alterations caused by arsenical exposure identifies potential new targets for treating arsenical-induced kidney injury (Moore et al, 2024).…”
mentioning
confidence: 99%